ANALISIS PENGARUH PENERAPAN BUDAYA TERHADAP KEBUTUHAN EKONOMI DAN PERILAKU MANAJEMEN KEUANGAN PADA MASYARAKAT ENDE LIO - Laurentius D. Gadi Djou; Apriana Marselina (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2020)
Indonesia is a country that has diverse tribes and cultures. Each culture has different behavioral characteristics in terms of financial management that can affect the economic growth of a region. Wurumana culture is a local custom of the Ende Lio community which is related to the cycle of money circulation in the family which has become a tradition for generations. The purpose of this study was to determine the effect of local culture (Wurumana) on Economic Needs, the effect of Economic Needs on Financial Management Behavior, the influence of Economic Needs on Financial Attitudes, and to determine the effect of Financial Attitudes on Financial Management Behavior of the Ende Lio community. The research method used in this study is a quantitative method using Structural Equation Modeling (SEM) analysis tools using AMOS 22. The results of the study show that Wurumana Culture has a significant positive effect on Economic Conditions (H1), Economic Conditions are proven to have a significant positive effect on Management Behavior Financial (H2), Economic Conditions have a significant positive effect on Financial Attitudes (H3), and Financial Attitudes have a significant positive effect on Financial Management Behavior (H4).